Innovations in the Physical Education of Schoolchildren - Sofiya Vlasova (Lesya Ukrainka Volyn National University, 2017)
The article is devoted to the problems of application of the innovative technologies in the system of physical education. Iinnovation in the education is the process of creating, dissemination and application of the new means (novelties) for the solving those pedagogical problems which have been solving before in a different way. Leading scientists suggested innovative technologies like Nordic walk, fit ball aerobic, healthy movably thematic games for solving the problems of educational valeological aiming of the physical education of the primary school children and other. Practical demonstration of the sports and health improvement                technologies in physical education is fitness programs. Application of the innovative sports and health improvement fitness technologies in the physical education process of the children of secondary school age will favor to increase of efficiency of both in school and after school work. Aerobic training is the most justified among the health building technologies. Therefore development of the programs aimed at sport and health improvement of this kind gain exceptional sense. Role skating is an effective means of improvement of health which involves a big number of muscles, without getting out aerobic regime of energy supply.